An in vitro investigation of the inflammatory response to the strain amplitudes which occur during high frequency oscillation ventilation and conventional mechanical ventilation. (9th May 2019) - Harris, Christopher; Thorpe, Stephen D.; Rushwan, Sara; Wang, Wei; Thompson, Clare L.; Peacock, Janet L.; Knight, Martin M.; Gooptu, Bibek; Greenough, Anne
Abstract: Children randomised in the neonatal period to high frequency oscillatory ventilation (HFOV) or conventional mechanical ventilation (CMV) in the United Kingdom Oscillation study (UKOS) had superior lung function at 11 to 14 years of age. During HFOV, much smaller tidal volumes, but a higher mean airway distending pressure is delivered, hence, a possible explanation for a volume dependent effect on long term lung function could be an increase in inflammation in response to higher tidal volumes and strains. We tested that hypothesis by assessing interleukin-6 (IL-6) and -8 (IL-8) release from A549 alveolar analogue cells following biaxial mechanical strain applied at 0.5 Hz occurring during conditions mimicking strain during CMV (5–20% strain) and conditions mimicking strain during HFOV (17.5% ± 2.5% strain) for up to 4 h. Cyclic strain of 5–20%, occurring during CMV, increased levels of both IL-6 and IL-8 compared to unstrained controls, while 17.5% ± 2.5% strain, occurring during HFOV, was associated with significantly lower levels of IL-6 (46.31 ± 2.66 versus 56.79 ± 3.73 pg/mL) and IL-8 (1340.2 ± 74.9 versus 2522 ± 248 pg/mL) secretion compared to conditions occurring during CMV at four hours. These results may provide a possible explanation for the superior lung function in 11–14-year-old children who had been supported in the neonatal period by HFOV.